COMMUNITY BASED APPROACH TO ASSESS FLOOD RISK PERCEPTION ALONG CODE RIVER - Diah Noor Heryanti; Nanette C. Kingma (Faculty of Geography, Universitas Gadjah Mada, 2012)
This p a p e r presents a flood risk perception and coping mechanism along CodeRiver, Yogyakarta Municipality based on the community approach. A total of 90households were interviewed. Data were analysed using Statistical Package for theSocial Sciences (SPSS) Program. The result indicated that there are no differencesof flood risk perception among the zones (p >.05). Perception of flood risk is influencedby several variables: gender, length of stay, RW’s risk level, distance betweenrespondents’ house and river and impact level of flood. Whereas, all types of community’scoping mechanism (technological, social, and economical) are influenced by impact levelof flood.